KOMPARASI PENENTUAN LOKASI PEMASANGAN KAPASITOR ANTARA GI. DUMAI DAN GI. BAGAN SIAPI-API - Hazri, M Wahyudi; Yulisman, Yulisman; Dwiharzandis, Aggrivina (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
During peak load conditions, significant voltage drops are observed in the Dumai transmission subsystem. The minimum voltages recorded at the Dumai, Bagan Siapi-api, and Dumai Industrial Area substations are 134.7 kV, 133.0 kV, and 131.1 kV, respectively, exceeding the permissible voltage deviation limits. To mitigate this condition, a shunt capacitor is designed and evaluated through modeling and simulation. Analytical and DigSILENT PowerFactory 2021 simulation results indicate that a 25 MVAR shunt capacitor installed at the Bagan Siapi-api Substation provides the most suitable compensation. The installation increases the bus voltage by 8.10 kV to 141.10 kV, corresponding to a voltage deviation of 5.93% from the nominal value. Furthermore, total system losses in the Riau subsystem are reduced from 20.63 MW and −352.8 MVAR to 19.88 MW and −366.8 MVAR, or reduction 0,75 MW. These results confirm that shunt capacitor integration effectively improves voltage profiles while reducing reactive power flow and system losses.Keywords: shunt capacitor, substation, voltage drop, DIgSILENT PowerFactory 2021, voltage improvement, system losses